Technical Assistance for Revitalizing High School Facilities and Infrastructure Based on Technical Guidelines Compliance - A. Ildha Dwi Puspita; Muhammad Arsyad Thaha; A. Nur Fitrianti (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2026)
The revitalization program of Senior High Schools (SMA) is a government initiative aimed at improving the quality of educational facilities and infrastructure to support a safe, comfortable, and sustainable learning environment. In its implementation, schools are not only beneficiaries but are also assigned responsibility by the Ministry of Primary and Secondary Education as the main executors of the revitalization activities, including workforce provision, supervision, and technical planning. This condition requires adequate technical capacity at the school level, while limited understanding of technical guidelines (juknis) may lead to inconsistencies in planning and construction implementation. This community service program aims to provide technical facilitation to one of the high schools implementing the revitalization program, namely SMAN 10 Gowa, in order to improve compliance with the applicable technical guidelines. The facilitation was carried out through a technical assistance approach without taking over the school’s role as the project implementer. The methods included reviewing technical guidelines and planning documents, conducting field inspections of construction works and facility completeness, and formulating as well as delivering technical recommendations discussed with the school implementation team. The evaluation was also carried out quantitatively by measuring the level of technical understanding before and after the assistance. The results indicate a significant improvement in the school’s technical understanding, as reflected by an increase from 50% in the pre-test to 90% in the post-test. In addition, the technical facilitation contributed to enhancing the school's understanding of revitalization technical requirements and encouraged adjustments in planning and construction practices to comply with the technical guidelines. This activity underscores the strategic role of universities in strengthening the technical capacity of schools as implementers of the revitalization program, as well as in supporting the improvement of quality and accountability in educational infrastructure development.